2011
DOI: 10.1194/jlr.m017582
|View full text |Cite
|
Sign up to set email alerts
|

Unique sphingomyelin patches are targets of a beta-cell-specific antibody

Abstract: This article is available online at http://www.jlr.org this restoration noninvasively ( 1 ). Recent years have seen exponential progress in applying various imaging modalities (MRI, positron emission tomography, optical) for noninvasive detection and monitoring of pancreatic ␤ -cell mass ( 2-6 ). A crucial prerequisite for clinical application of these techniques is the availability of a contrast agent with high affi nity and high specifi city toward ␤ -cell surface markers.Antibodies or their fragments, owing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…We recently reported the discovery of cholesterol-stabilized sphingomyelin patches on the surface of beta-cells that are targeted by IC2, a rat monoclonal antibody (Kavishwar et al 2011). In this study, we investigated whether the expression of these patches vary during diabetes development.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported the discovery of cholesterol-stabilized sphingomyelin patches on the surface of beta-cells that are targeted by IC2, a rat monoclonal antibody (Kavishwar et al 2011). In this study, we investigated whether the expression of these patches vary during diabetes development.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown the utility of the IC2 antibody in determining beta cell mass ex vivo in an STZ model of diabetes (Moore et al 2001). To fully exploit the value of this antibody or its fragments for imaging and/or targeted therapy we have recently elucidated the antigen for this antibody (Kavishwar et al 2011). In particular, we showed that sphingomyelin stabilized with cholesterol forms unique patches on the surface of beta-cells that are recognized by the IC2 antibody.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations